LIFI based Voice transmission for Coal Mine Safety Monitoring and Control Automation - S, Janaki; E, Aarthi; R, Chandiya; Bharathi J, Divya; K, Jayashree (International Journal of Engineering and Technology, 2018)
Lightweight Mash up for Coal Mine Safety Moni- toring and Control Automation This paper plans an observing framework for coal mine dependent on LIFI transmission. The checking framework gathers temperature, gas level underground of coal mine through sensor hubs around the mine, and after  that transmits the information to the data handling terminal dependent on . What’s more, the client can move the data in  voice motion through LI-FI. Additionally, four sorts of  coal  mine security checking and control computerization situations are represented, and the execution has likewise been estimated and investigated. It has been demonstrated that our lightweight concoction middle ware can diminish the expenses proficiently to make coal mine observing and control applications.